Anti-Inflammatory Effects of HDL (High-Density Lipoprotein) in Macrophages Predominate Over Proinflammatory Effects in Atherosclerotic Plaques. Issue 12 (December 2019) - Fotakis, Panagiotis; Kothari, Vishal; Thomas, David G.; Westerterp, Marit; Molusky, Matthew M.; Altin, Elissa; Abramowicz, Sandra; Wang, Nan; He, Yi; Heinecke, Jay W.; Bornfeldt, Karin E.; Tall, Alan R.
Abstract : Objective: HDL (high-density lipoprotein) infusion reduces atherosclerosis in animal models and is being evaluated as a treatment in humans. Studies have shown either anti- or proinflammatory effects of HDL in macrophages, and there is no consensus on the underlying mechanisms. Here, we interrogate the effects of HDL on inflammatory gene expression in macrophages. Approach and Results: We cultured bone marrow–derived macrophages, treated them with reconstituted HDL or HDL isolated from APOA1 Tg ;Ldlr −/− mice, and challenged them with lipopolysaccharide. Transcriptional profiling showed that HDL exerts a broad anti-inflammatory effect on lipopolysaccharide-induced genes and proinflammatory effect in a subset of genes enriched for chemokines. Cholesterol removal by POPC (1-palmitoyl-2-oleoyl-glycero-3-phosphocholine) liposomes or β-methylcyclodextrin mimicked both pro- and anti-inflammatory effects of HDL, whereas cholesterol loading by POPC/cholesterol-liposomes or acetylated LDL (low-density lipoprotein) before HDL attenuated these effects, indicating that these responses are mediated by cholesterol efflux. While early anti-inflammatory effects reflect reduced TLR (Toll-like receptor) 4 levels, late anti-inflammatory effects are due to reduced IFN (interferon) receptor signaling. Proinflammatory effects occur late and represent a modified endoplasmic reticulum stress response, mediated by IRE1a (inositol-requiring enzyme 1a)/ASK1 (apoptosis signal-regulating kinase 1)/p38 MAPK (p38 mitogen-activated protein kinase) signaling, that occurs under conditions of extreme cholesterol depletion. To investigate the effects of HDL on inflammatory gene expression in myeloid cells in atherosclerotic lesions, we injected reconstituted HDL into Apoe −/− or Ldlr −/− mice fed a Western-type diet. Reconstituted HDL infusions produced anti-inflammatory effects in lesion macrophages without any evidence of proinflammatory effects. Conclusions: Reconstituted HDL infusions in hypercholesterolemic atherosclerotic mice produced anti-inflammatory effects in lesion macrophages suggesting a beneficial therapeutic effect of HDL in vivo. Abstract : Supplemental Digital Content is available in the text.